The Use of Miswak as Toothbrush for Orthodontic Patient - Ismail, Khoirulzariah (Hindawi Publishing Corporation, 2016)
This case report presents a patient who is undergoing orthodontic treatment with upper and lower fixed appliance. An interesting point on this case is that the patient only usesMiswak as her oral hygiene tool due to her religious belief.The oral hygiene protocol was allowed and her oral health was closely monitored throughout her orthodontic treatment.